Ordered porous carbon and preparation method thereof

By preparing the ordered porous carbon material PFC-Si-X-Y with mesoporous structure, the existing low-temperature SCR denitrification catalyst has been solved, and the application limitation and cost of existing low-temperature SCR denitrification catalysts are limited and cost-effective, achieving high-efficiency denitrification effect in the field of flue gas treatment .

CN119118124APending Publication Date: 2024-12-13宝武水务科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256672.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing low-temperature SCR denitrification catalysts have limited applications below 200°C and are relatively expensive, making it difficult to widely promote them in the field of flue gas treatment.

Method used

The ordered porous carbon material PFC-Si-X-Y is used, which is prepared by phenol, NaOH and nano SiO2 and has a mesoporous structure and excellent denitrification properties. It is used as a low-temperature SCR denitrification catalyst.

Benefits of technology

It realizes low-temperature SCR denitrification performance that works effectively below 200℃, and reduces the production cost of the catalyst, which has important practical significance and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118124A_ABST
    Figure CN119118124A_ABST
Patent Text Reader

Abstract

The invention provides ordered porous carbon and a preparation method thereof, and the preparation method comprises the following steps: melting phenol into liquid to obtain a first solution; adding NaOH into the first solution, and heating to obtain a second solution; adding nano SiO2 with a preset particle size into the second solution, and reacting at a first preset temperature for a second preset time to obtain a third solution of which the weight percentage of SiO2 is a first preset value; adding a formaldehyde aqueous solution into the third solution, heating and reacting to obtain a fourth solution; curing the fourth solution to obtain a first solid; crushing and carbonizing the first solid to obtain first powder; siO2 in the first powder is removed, and second powder is obtained; sequentially activating, washing and drying the second powder to obtain fourth powder. The ordered porous carbon provided by the invention has a mesoporous structure, has channels or holes with a certain size, has excellent denitration performance, and can be used as a low-temperature SCR denitration catalyst; the preparation method disclosed by the invention has the advantages of simplicity and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flue gas catalytic denitration, and in particular to an ordered porous carbon and a preparation method thereof. Background Art

[0002] In the context of the rapid development of new energy and the dual carbon goals, my country's air pollutant emissions will be greatly reduced in the long run. However, before 2030, the emissions of air pollutants from traditional fossil fuels such as coal and oil that need to be controlled in my country will still increase, and it is urgent to control the emission of nitrogen oxides. X ) is the general term for NO, NO2, N2O, and N2O5. This type of pollutant can quickly destroy the ozone layer and bring about severe weather such as photochemical smog and acid rain. It has also been proven to be a key factor in the formation of smog weather. X It can enter the human body through the respiratory or skin system, dissolve and accumulate in the alveolar fluid, and partially convert into nitrates or nitrites to corrode lung tissue; nitrites can also spread to the blood system, combine with hemoglobin to form methemoglobin, causing the human body to lack oxygen and suffocate. X The production of NO can be divided into natural and artificial production. X It is usually produced by lightning, soil microorganisms, etc. X Most come from the burning of fossil fuels for power generation, transportation and other incineration processes.

[0003] NO X Emission reduction methods can be divided into pre-combustion treatment, combustion control and post-combustion treatment. Pre-combustion treatment and combustion control can only achieve NO X The most commonly used technologies for the removal of low NOx emissions are selective non-catalytic reduction (SNCR) and selective catalytic reduction (SCR). SNCR has a high operating temperature but low denitrification efficiency and is suitable for power plants with lower emissions. The selective catalytic reduction (SCR) denitrification technology using NH3 as a reducing agent is currently the most popular technology for removing NOx from flue gas. X The mainstream technology for purification is referred to as NH3-SCR denitration technology. However, the mature denitration catalyst developed by thermal power plants cannot be further promoted and applied in low temperature (<250℃) occasions (sintering, pelletizing, kilns, etc.) due to its narrow temperature window (300-400℃). Therefore, the development of low-temperature SCR denitration catalysts that can work below 200℃ has important practical significance and application value. In addition, low-temperature SCR denitration catalysts can also be promoted and applied as an important part of the ultra-low emission technology currently being vigorously promoted by the country. Summary of the invention

[0004] The purpose of the present invention is to provide an ordered porous carbon and a preparation method thereof, so that the ordered porous carbon has a mesoporous structure and has channels or holes of a certain size, has excellent denitration performance, can be used as a low-temperature SCR denitration catalyst, and can work effectively at temperatures below 200°C.

[0005] In order to achieve the above object, the present invention provides a method for preparing ordered porous carbon, which comprises:

[0006] Melting phenol into liquid to obtain a first solution;

[0007] adding NaOH to the first solution and heating for a first preset time to obtain a second solution;

[0008] Adding nano-SiO2 of a preset particle size into the second solution, reacting at a first preset temperature for a second preset time, to obtain a third solution with a weight percentage of SiO2 of a first preset value;

[0009] adding formaldehyde aqueous solution to the third solution, heating and reacting for a third preset time to obtain a fourth solution;

[0010] solidifying the fourth solution to obtain a first solid;

[0011] crushing and carbonizing the first solid to obtain a first powder;

[0012] Removing SiO2 from the first powder to obtain a second powder;

[0013] The second powder is activated, washed and dried in sequence to obtain a fourth powder.

[0014] Optionally, the weight percentage of formaldehyde in the formaldehyde aqueous solution is 30wt% to 40wt%, and the molar ratio of phenol, formaldehyde and NaOH is 1:(1 to 1.4):(0.08 to 0.12).

[0015] Optionally, the method of adding the formaldehyde aqueous solution to the third solution for heating and reacting for the third preset time includes: after adding the formaldehyde aqueous solution to the third solution, heating to above 75° C. and below 95° C. and reacting for the third preset time, wherein the third preset time is 50 min to 70 min.

[0016] Optionally, the method for solidifying the fourth solution includes: transferring the fourth solution into a homogeneous reactor, maintaining a constant temperature for 11 hours to 13 hours at a third preset temperature within a range of 55°C to 65°C, then heating to 150°C to 170°C to obtain a nano-SiO2 phenolic resin composite material, and then cooling to a fourth preset temperature to obtain the first solid.

[0017] Optionally, the method for obtaining the first powder includes: placing the crushed first solid in an inert atmosphere, heating the temperature of the cavity where the first solid is located to 430°C to 470°C and then keeping it warm for 2.5h to 3.5h, then heating it to 880°C to 920°C and keeping it warm for 1.5h to 2.5h, to obtain the first powder.

[0018] Optionally, the method for removing SiO2 in the first powder includes: placing the first powder in an alkaline solution, maintaining the solution at a second preset temperature for a fourth preset time and stirring the solution, thereby etching away SiO2 in the first powder to obtain a fifth solution.

[0019] Optionally, the method for obtaining the second powder includes: cooling the fifth solution to a fifth preset temperature, adjusting the pH value of the cooled fifth solution to neutral to obtain a sixth solution, and drying the sixth solution to obtain the second powder.

[0020] Optionally, the method for obtaining the fourth powder includes: activating the second powder with KOH to obtain a third powder, washing the third powder by suction filtration to obtain a neutral filtrate, and drying the neutral filtrate to obtain the fourth powder.

[0021] Based on another aspect of the present invention, the present invention also provides an ordered porous carbon, which is obtained by the method as described above, and the general formula of the porous carbon is PFC-Si-XY, wherein X is the particle size of nano-SiO2, Y is the first preset value, and PFC is phenolic resin carbon.

[0022] Optionally, 15nm≤X≤25nm, 2wt%≤Y≤6wt%.

[0023] Configured as above, the ordered porous carbon of the present invention has a mesoporous structure and has pores or holes of a certain size, which can provide a larger specific surface area and more active sites, help to improve the catalytic activity and selectivity, promote the diffusion and mass transfer process of the reactants, and have excellent denitrification performance. The ordered porous carbon of the present invention can be used as a low-temperature SCR denitrification catalyst and can work effectively at temperatures below 200°C; the present invention adopts a unique formula and process, has the advantages of simple method and low cost, effectively alleviates the bottleneck problem of the relatively high cost of the current low-temperature SCR denitrification catalyst, and is expected to play a greater role in the field of flue gas treatment, and has important practical significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Those skilled in the art should understand that the drawings are provided for a better understanding of the present invention and do not constitute any limitation on the scope of the present invention.

[0025] Figure 1 A schematic diagram of an ordered porous carbon and a preparation method thereof according to an embodiment of the present invention;

[0026] Figure 2 The NO of the PFC-Si-XY samples prepared in Examples 1 to 6 of the present invention at different temperatures X Line chart of conversion rate;

[0027] Figure 3 XRD patterns of the PFC-Si-XY samples prepared in Examples 1 to 6;

[0028] Figure 4 This is a scanning electron microscope image of the sample PFC-Si-15-2 at a scale of 10 μm;

[0029] Figure 5 This is a scanning electron microscope image of the sample PFC-Si-15-4 at a scale of 10 μm;

[0030] Figure 6 This is a scanning electron microscope image of the sample PFC-Si-15-6 at a scale of 10 μm;

[0031] Figure 7 This is the SEM image of the sample PFC-Si-20-2 at 10 μm scale;

[0032] Figure 8 This is a scanning electron microscope image of the sample PFC-Si-20-4 at a scale of 10 μm;

[0033] Fig. 9 This is a scanning electron microscope image of the sample PFC-Si-20-6 at a scale of 10 μm;

[0034] Fig.10 The nitrogen adsorption-desorption curves of the PFC-Si-XY samples prepared in Examples 1 to 6 are shown;

[0035] Fig.11 This is the pore size distribution diagram of the PFC-Si-XY samples prepared in Examples 1 to 6. DETAILED DESCRIPTION

[0036] In this document, unless otherwise specified, the terms "upper", "lower", "left", "right", "inside", "outside", "front", "back", "top", "bottom", etc. are used to indicate directions or positional relationships based on the drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction and operation. Therefore, they cannot be understood as limiting the present invention.

[0037] The specific implementation of the present invention will be described in more detail below in conjunction with the schematic diagram. The advantages and features of the present invention will become clearer based on the following description. It should be noted that the drawings are all in a very simplified form and are not in exact proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.

[0038] Figure 1 Schematic diagram of ordered porous carbon and its preparation method according to an embodiment of the present invention. Figure 1 An embodiment of the present invention provides a method for preparing ordered porous carbon, which includes step S1, step S2, step S3, step S4, step S5, step S6, step S7 and step S8. Step S1, step S2, step S3, step S4, step S5, step S6, step S7 and step S8 are described in detail below.

[0039] Step S1: Melting phenol into liquid to obtain a first solution.

[0040] Specifically, a certain amount of phenol is weighed and added into a flask, and heated to melt it. For example, it can be heated in a water bath or an oil bath, and the temperature is maintained at 45° C. to 55° C. to melt the phenol into a liquid state, thereby obtaining a first solution.

[0041] Step S2: Add NaOH to the first solution and heat for a first preset time (the heating temperature may be 50° C.) to obtain a second solution. NaOH is used as a catalyst, and a magnetic stirring method may be used after adding NaOH to accelerate dissolution. The first preset time may be 20 to 40 minutes.

[0042] Step S3: Add nano-SiO2 of a preset particle size to the second solution, react at a first preset temperature for a second preset time (stirring may be performed simultaneously), and obtain a third solution in which the weight percentage of SiO2 is the first preset value. It is understood that nano-SiO2 is used as a template for pore formation, and the particle size of nano-SiO2 directly affects the pore size of porous carbon. The first preset temperature may be 40°C to 60°C, and the second preset time may be determined according to actual conditions, for example, the second preset time may be 30 minutes to 60 minutes.

[0043] Step S4: adding the formaldehyde aqueous solution to the third solution, heating and reacting for a third preset time to obtain a fourth solution. Specifically, the weight percentage of formaldehyde in the formaldehyde aqueous solution is 30wt% to 40wt%, and the molar ratio of phenol, formaldehyde and NaOH is 1:(1 to 1.4):(0.08 to 0.12). For example, the weight percentage of formaldehyde in the formaldehyde aqueous solution may be 37wt%, and the molar ratio of phenol, formaldehyde and NaOH may be 1:1.2:0.1.

[0044] Further, the method of adding the formaldehyde aqueous solution to the third solution for heating and reacting for a third preset time includes: after adding the formaldehyde aqueous solution to the third solution, heating to above 75° C. and below 95° C. and reacting for a third preset time, the third preset time is 50 min to 70 min, and the third preset time can be, for example, one hour. Since the reaction is exothermic, condensed water can be used to adjust the temperature during the reaction to ensure that the temperature is not higher than 95° C.

[0045] Step S5: solidifying the fourth solution to obtain a first solid.

[0046] For example, the method for solidifying the fourth solution includes: pouring the fourth solution into a culture dish, the material of the culture dish can be polytetrafluoroethylene. The culture dish filled with the fourth solution is transferred to a homogeneous reactor, and the third preset temperature is kept at a constant temperature for 11h to 13h, the third preset temperature is within 55°C to 65°C, and then heated to 150°C to 170°C to obtain nano-SiO2 phenolic resin (thermosetting resin) composite material, and then cooled to the fourth preset temperature to obtain the first solid. For example, in the present embodiment, the homogeneous reactor is kept at a constant temperature for 12h at 60°C, and then the staged heating mode is adopted to heat up to 160°C, such as gradually heating up from 60°C to 160°C at a heating rate of 10°C / h to obtain nano-SiO2 phenolic resin composite material, and then cooled to the fourth preset temperature, the fourth preset temperature is room temperature, and the room temperature can be 10°C-35°C.

[0047] Step S6: crushing and carbonizing the first solid to obtain a first powder. The crushing can be performed by a roller compactor.

[0048] The method for obtaining the first powder includes: placing the crushed first solid in an inert atmosphere, raising the temperature of the cavity where the first solid is located from room temperature to 430°C to 470°C and then keeping it warm for 2.5h to 3.5h, and then raising the temperature to 880°C to 920°C and then keeping it warm for 1.5h to 2.5h, to obtain the first powder. For example, the temperature of the cavity where the first solid is located is raised from room temperature to 450°C and then kept warm for 3 hours, and then raised to 900°C and then kept warm for 2 hours, thereby carbonizing to obtain the first powder. The heating method can be 5°C / min.

[0049] Step S7: removing SiO2 from the first powder to obtain a second powder.

[0050] Specifically, the method for removing SiO2 in the first powder includes: placing the first powder in an alkaline solution, maintaining the fourth preset time at a second preset temperature and stirring, thereby etching and removing SiO2 in the first powder to obtain a fifth solution. Exemplarily, the alkaline solution can be a 5M sodium hydroxide solution, that is, a sodium hydroxide solution with a sodium hydroxide concentration of 5 mol per liter. The second preset temperature is 45°C to 55°C, and the fourth preset time is 9-11h. For example, after placing the first powder in the alkaline solution, maintain 50°C and stir for 10 hours, thereby etching and removing the SiO2 template.

[0051] Furthermore, the method for obtaining the second powder includes: cooling the fifth solution to a fifth preset temperature, the fifth preset temperature being room temperature, and adjusting the pH value of the cooled fifth solution to neutral to obtain a sixth solution. For example, after the fifth solution is cooled to room temperature, the fifth solution is washed with hydrochloric acid and deionized water to neutrality. The sixth solution is dried to obtain the second powder.

[0052] Step S8: activating, washing and drying the second powder in sequence to obtain a fourth powder.

[0053] Specifically, the method for obtaining the fourth powder includes: activating the second powder with KOH (potassium hydroxide) to obtain the third powder, washing the third powder by suction filtration to obtain a neutral filtrate, and drying the neutral filtrate to obtain the fourth powder. For example, KOH and the second powder are mixed at an alkali-carbon ratio of 4:1 and transferred to a tubular furnace (or other furnace body), and nitrogen is purged in the furnace, and the flow rate of the nitrogen purge is 70-100mL / min, such as the flow rate of the nitrogen purge can be 80mL / min, and the tubular furnace is heated from room temperature to the sixth preset temperature at a rate of 5℃ / min, and maintained at the sixth preset temperature for 60-120 minutes for activation, such as 90 minutes. The sixth preset temperature is within 600-820℃, such as the sixth preset temperature can be 800℃. The method for drying the neutral filtrate can be to transfer the neutral filtrate to a 100℃ oven and dry it for 11-13h, such as drying it for 12 hours, thereby obtaining the fourth powder. Preferably, the fourth powder can be ground and sieved to obtain 40-60 mesh particles to improve the catalytic effect on denitration.

[0054] In summary, the present invention uses SiO2 as a hard template, phenolic resin as a carbon precursor, and solid alkali as a catalyst, and obtains a thermosetting resin after thermal curing, and then removes the SiO2 template by alkali washing after carbonization, and then washes to neutrality and dries to obtain a second powder, and then activates, filters, and dries to obtain a fourth powder. The fourth powder is the porous carbon prepared by the present invention.

[0055] Based on another aspect of the present invention, the present invention also provides an ordered porous carbon, which is obtained by the above method. The general formula of the porous carbon is PFC-Si-XY, wherein X is the particle size of nano-SiO2, Y is a first preset value, and PFC is phenolic resin carbon.

[0056] Optionally, 15nm≤X≤25nm, 2wt%≤Y≤6wt%.

[0057] Configured as above, the ordered porous carbon of the present invention has a mesoporous structure and has pores or holes of a certain size, which can provide a larger specific surface area and more active sites, help to improve the catalytic activity and selectivity, promote the diffusion and mass transfer process of the reactants, and have excellent denitrification performance. The ordered porous carbon of the present invention can be used as a low-temperature SCR denitrification catalyst and can work effectively at temperatures below 200°C; the present invention adopts a unique formula and process, has the advantages of simple method and low cost, effectively alleviates the bottleneck problem of the relatively high cost of the current low-temperature SCR denitrification catalyst, and is expected to play a greater role in the field of flue gas treatment, and has important practical significance and application value.

[0058] The present invention will be further described in detail below with reference to the embodiments.

[0059] Example 1

[0060] Weigh 18.82g phenol and add it to a flask, place it in an oil bath and keep it at 50°C to melt phenol to a liquid, weigh 0.8g of NaOH according to the molar ratio of NaOH to phenol of 0.1:1 and add it to the phenol liquid, stir it magnetically until it is completely dissolved, keep it in a 50°C water bath for 30min, then weigh nano-SiO2 with a particle size X of 15nm and add it to the above solution, so that the weight percentage of SiO2 in the third solution is 2wt%, that is, Y is 2wt%. Stir it magnetically and keep it in a 50°C water bath for 60min to obtain the third solution. Subsequently, weigh 18.6673g of 37wt% formaldehyde aqueous solution according to the molar ratio of phenol to formaldehyde of 1:1.2, add it to the third solution, warm it to 75°C and fully react for 60min, and because the reaction is exothermic, it is necessary to adjust it with condensed water to ensure that the temperature is not higher than 95°C to obtain the fourth solution. The fourth solution was poured into a petri dish and transferred into a homogeneous reactor, kept at a constant temperature of 60°C for 12 hours, and then cured by stepwise heating, gradually heated from 60°C to 160°C at a heating rate of 10°C / h to obtain a nano-SiO2 phenolic resin composite material, crushed and carbonized the obtained material to obtain a first powder, transferred the first powder to a 5M NaOH solution, magnetically stirred in a 50°C water bath for 10 hours, and etched to remove the silica template to obtain a fifth solution. After the fifth solution was cooled to room temperature, it was washed with HCl and deionized water to neutrality, and then dried to obtain a second powder. Finally, the second powder was mechanically mixed with KOH at a mass ratio of 1:4, heated to the sixth preset temperature under a N2 purge of 80-100mL / min in a horizontal furnace and maintained for 60-120min for activation. After activation is completed, a third powder is obtained, the third powder is filtered and washed until the filtrate is neutral, and then dried in an oven at 100° C. for 12 h to obtain a fourth powder.

[0061] Example 2

[0062] The operation method is the same as that of Example 1, except that the amount of nano-SiO2 added is different, so that the weight percentage of SiO2 in the third solution is 4wt%, that is, Y is 4wt%. The particle size X of the added nano-SiO2 is still 15nm.

[0063] Example 3

[0064] The operation method is the same as that of Example 1, except that the amount of nano-SiO2 added is different, so that the weight percentage of SiO2 in the third solution is 6wt%, that is, Y is 6wt%. The particle size X of the added nano-SiO2 is still 15nm.

[0065] Example 4

[0066] The operation method is the same as that of Example 1, except that the particle size X of the added nano-SiO2 is different, and the particle size X is 20 nm. The weight percentage of SiO2 in the third solution is still 2wt%, that is, Y is 2wt%.

[0067] Example 5

[0068] The operation method is the same as that of Example 1, except that the particle size X of the added nano-SiO2 is 20 nm, so that the weight percentage of SiO2 in the third solution is 4wt%, that is, Y is 4wt%.

[0069] Example 6

[0070] The operation method is the same as that of Example 1, except that the particle size X of the added nano-SiO2 is 20 nm, so that the weight percentage of SiO2 in the third solution is 6wt%, that is, Y is 6wt%.

[0071] The fourth powder prepared in Example 1 is sample PFC-Si-15-2, the fourth powder prepared in Example 2 is sample PFC-Si-15-4, the fourth powder prepared in Example 3 is sample PFC-Si-15-6, the fourth powder prepared in Example 4 is sample PFC-Si-20-2, the fourth powder prepared in Example 5 is sample PFC-Si-20-4, and the fourth powder prepared in Example 6 is sample PFC-Si-20-6.

[0072] No X The conversion rate is used as an evaluation index of the catalytic activity of the samples PFC-Si-15-2, PFC-Si-15-4, PFC-Si-15-6, PFC-Si-20-2, PFC-Si-20-4 and PFC-Si-20-6, and a denitrification evaluation experiment is conducted. The specific method includes: grinding and sieving the sample PFC-Si-15-2 prepared in Example 1 into a particle size of 40 to 60 mesh, weighing 1.5 ml of the sample PFC-Si-15-2 and placing it in a quartz tube with both ends open, filling both ends of the quartz tube with quartz sand and quartz wool, and then placing the quartz tube in a reaction device. A mixed gas containing NH3, NO, O2 and N2 is introduced into the reaction device, the total flow rate of the mixed gas is 100 ml / min-300 ml / min, and the reaction temperature is 100°C-220°C. N2 is used as a balance gas, and the reaction space velocity is about 12000 h -1, the concentrations of the components in the mixed gas are: 500ppmNO (ppmNO represents the volume concentration of NO, i.e. parts per million or parts per million), 600ppmNH3 (ppmNH3 represents the volume concentration of NH3, i.e. parts per million or parts per million), 5.5Vol.%O2 (Vol.%O2 represents the volume concentration of O2, i.e. percentage). NO X The conversion rate is calculated as follows:

[0073]

[0074] Among them, C in is the NO at the inlet of the reaction equipment X The concentration, C out is the NO at the outlet of the reaction equipment X The concentration of NO at different temperatures was calculated. X Conversion rate.

[0075] The same operation was performed on the samples prepared in Examples 2 to 6, and the NO values ​​when using samples PFC-Si-15-2, PFC-Si-15-4, PFC-Si-15-6, PFC-Si-20-2, PFC-Si-20-4 and PFC-Si-20-6 as denitration catalysts were plotted. X The conversion rate and temperature curve, such as Figure 2 , the horizontal axis is the reaction temperature, and the vertical axis is NO X Conversion rate. 15-2 in the figure shows the curve when the sample PFC-Si-15-2 is used as a denitrification catalyst. The same is true for 15-4, 15-6, 20-2, 20-4 and 20-6 in the figure. Figure 2 The performance of the PFC-Si-XY sample prepared by the present invention in the denitration evaluation experiment shows that the catalyst with the best performance is the sample PFC-Si-15-4 in Example 2. Within the reaction temperature range of 180°C-220°C, the denitration efficiency of the sample PFC-Si-15-4 is always maintained at a high level, especially at around 220°C. X The conversion rate reached the highest value, far exceeding that of other samples.

[0076] Figure 3 The XRD diagrams of the PFC-Si-XY samples prepared in Examples 1 to 6 are shown in Figure 15-2, which represents the sample PFC-Si-15-2, and the same is true for Figures 15-4, 15-6, 20-2, 20-4 and 20-6. It can be understood that XRD (X-ray diffraction) analysis uses the characteristics of X-rays to deeply explore the microstructure inside a substance. Figure 3The horizontal axis 2θ represents the diffraction angle, and the vertical axis Intensity represents it. It can be seen from the figure that diffraction peaks with weaker intensity appear at around 2θ=23° and 44°, which are the characteristic diffraction peaks of the (002) and (100) lattice planes of the sample, respectively. This result shows that the prepared sample is mainly composed of amorphous carbon groups and graphite crystals.

[0077] Figures 4 to 9 The morphology of nano-SiO2 / phenolic resin carbon materials (a) sample PFC-Si-15-2, (b) sample PFC-Si-15-4, (c) sample PFC-Si-15-6, (d) sample PFC-Si-20-2, (e) sample PFC-Si-20-4 and (f) sample PFC-Si-20-6 at 10 μm, respectively. The 10 μm in the figure is the electron microscope scale. Figures 4 to 9 It can be seen that all samples prepared in the present invention exhibit similar morphological structures, consisting of tightly packed blocks.

[0078] Furthermore, nitrogen adsorption and desorption can be used to detect the pore size, pore volume and other structural characteristic parameters of the sample. Fig.10 The nitrogen adsorption-desorption curves of the PFC-Si-XY samples prepared in Examples 1 to 6 are shown in Figure 15-2, which represents the sample PFC-Si-15-2. The same is true for Figures 15-4, 15-6, 20-2, 20-4 and 20-6. The horizontal axis represents the relative pressure (RelativePressure) and the vertical axis represents the adsorption amount (Quantity absorbed). It can be understood that in the nitrogen adsorption-desorption curve, the relative pressure is usually expressed as P / P0, where P is the actual pressure of nitrogen on the sample and P0 is the saturated vapor pressure of nitrogen at the same temperature; the adsorption amount refers to the amount of nitrogen adsorbed by the sample under a certain pressure, usually expressed as the volume of nitrogen adsorbed per unit mass of the sample (such as cm 3 / gSTP). Fig.10 It can be clearly observed that these curves show typical type IV characteristics and are accompanied by obvious hysteresis loops, indicating that these samples all have mesoporous structures and the presence of pores or holes of a certain size, which can provide a larger specific surface area and more active sites, help improve catalytic activity and selectivity, and promote the diffusion and mass transfer process of reactants.

[0079] Fig.11The pore size distribution diagram of the PFC-Si-XY samples prepared in Examples 1 to 6, 15-2 in the figure represents the sample PFC-Si-15-2, and 15-4, 15-6, 20-2, 20-4 and 20-6 in the figure are the same. The horizontal axis Pore size is the pore size, and the vertical axis BJH dV / dD Pore Volume represents the rate of change of the differential pore volume with the pore size, reflecting the change of the pore volume at a specific pore size, specifically, reflecting the change of the pore volume under the unit pore size change. It can be understood that in the analysis of pore size distribution data, the BJH method is a commonly used analysis method for analyzing the pore size distribution of porous materials. Fig.11 The pore structure characteristics of these samples are shown in detail, further revealing the reasons for their superior catalytic performance. Fig.11 It can be seen that the pore sizes of these samples are mainly distributed in the range of 1-10nm, corresponding to aggregated mesopores, and all show a relatively concentrated distribution trend, indicating that the pore structure of these samples has good uniformity. This uniformity helps to improve the overall performance of the material, making it show higher efficiency and stability in practical applications.

[0080]

[0081] Table 1

[0082] Table 1 shows the specific surface areas S of samples PFC-Si-15-2, PFC-Si-15-4, PFC-Si-15-6, PFC-Si-20-2, PFC-Si-20-4 and PFC-Si-20-6 obtained using the BET (Brunauer-Emmett-Teller) model and the BJH (Barrett-Joyner-Halenda) calculation method. BET (m 2 / g), total pore volume V total (cm 3 / g), average pore diameter (nm). It can be seen from Table 1 that when the doping amount of nano-SiO2 is too much, the excess nanoparticles will agglomerate in the resin matrix and form coating points, thereby increasing the pore diameter of the composite material. Generally, the surface area is related to the internal structure or porosity of the support, and the active sites are often distributed on the inner surface. At the active sites, the reactants are physically and chemically adsorbed on the catalyst surface. Before being adsorbed, the reactant molecules must diffuse through the catalyst pores to reach the inner surface. Among them, the sample PFC-Si-15-2 has the largest specific surface area of ​​1428.2m 2 / g. But by Figure 2It can be seen that the denitrification activity of sample PFC-Si-15-2 is not good, which shows that specific surface area is not the only factor affecting denitrification activity. The catalytic ability of a catalyst does not only depend on its surface area, porosity and pore diameter. Generally, smaller pores can increase the surface area and catalytic activity by providing additional active sites on the catalyst surface, but too small pores may hinder the diffusion of reactant molecules. It is understandable that the preparation process and conditions will affect the pore size distribution. By adjusting the parameters in the preparation process, such as silicon source, catalyst, temperature, etc., the pore size distribution can be effectively regulated. This discovery provides more possibilities for the preparation and application of porous carbon materials.

[0083] In summary, sample PFC-Si-15-4 has the best catalytic performance as a denitrification catalyst.

[0084] It should be noted that references to "one embodiment", "an embodiment", "a specific embodiment", "some embodiments", etc. in the specification only indicate that the described embodiment may include a particular feature, structure or characteristic. Moreover, such phrases do not necessarily refer to the same embodiment. In addition, when a particular feature, structure or characteristic is described in conjunction with an embodiment, whether or not explicitly described, it is within the knowledge of a person skilled in the relevant art to implement such feature, structure or characteristic in conjunction with other embodiments.

[0085] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments, and the same or similar parts between the various embodiments can be referred to each other. For the system disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.

[0086] It should also be noted that, although the present invention has been disclosed as a preferred embodiment, the above embodiment is not intended to limit the present invention. For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

[0087] It should also be understood that, unless otherwise specified or indicated, the terms "first", "second", "third", etc. in the specification are merely used to distinguish between the various components, elements, steps, etc. in the specification, and are not used to indicate the logical relationship or sequential relationship between the various components, elements, steps, etc.

[0088] It should also be recognized that the terms described herein are only used to describe specific embodiments and are not intended to limit the scope of the invention. It should be noted that the singular forms "a" and "an" used herein and in the appended claims include plural references unless the context clearly indicates otherwise. For example, a reference to "a step" or "a device" means a reference to one or more steps or devices, and may include secondary steps and secondary devices. All conjunctions used should be understood in the broadest sense. And, the word "or" should be understood to have the definition of a logical "or", rather than a logical "exclusive or", unless the context clearly indicates otherwise. In addition, the implementation of the method and / or device in the embodiments of the present invention may include performing the selected task manually, automatically, or in combination.

Claims

1. A method for preparing ordered porous carbon, characterized in that: include: Melting phenol into liquid to obtain a first solution; Adding NaOH to the first solution and heating for a first preset time to obtain a second solution; Adding nano-SiO2 of a preset particle size into the second solution, reacting at a first preset temperature for a second preset time, to obtain a third solution with a weight percentage of SiO2 of a first preset value; adding formaldehyde aqueous solution to the third solution, heating and reacting for a third preset time to obtain a fourth solution; solidifying the fourth solution to obtain a first solid; crushing and carbonizing the first solid to obtain a first powder; Removing SiO2 from the first powder to obtain a second powder; The second powder is activated, washed and dried in sequence to obtain a fourth powder.

2. The method for preparing ordered porous carbon according to claim 1, characterized in that: The weight percentage of formaldehyde in the formaldehyde aqueous solution is 30wt% to 40wt%, and the molar ratio of phenol, formaldehyde and NaOH is 1:(1-1.4):(0.08-0.12).

3. The method for preparing ordered porous carbon according to claim 1, characterized in that: The method of adding the formaldehyde aqueous solution to the third solution for heating and reacting for the third preset time includes: after adding the formaldehyde aqueous solution to the third solution, heating to above 75° C. and below 95° C. and reacting for the third preset time, wherein the third preset time is 50 min to 70 min.

4. The method for preparing ordered porous carbon according to claim 1, characterized in that: The method for solidifying the fourth solution includes: transferring the fourth solution into a homogeneous reactor, maintaining the temperature at a third preset temperature for 11 hours to 13 hours, wherein the third preset temperature is within the range of 55°C to 65°C, then heating the temperature to 150°C to 170°C to obtain a nano-SiO2 phenolic resin composite material, and then cooling the solution to a fourth preset temperature to obtain the first solid.

5. The method for preparing ordered porous carbon according to claim 1, characterized in that: The method for obtaining the first powder includes: placing the crushed first solid in an inert atmosphere, heating the cavity where the first solid is located to 430°C to 470°C and then keeping it warm for 2.5h to 3.5h, and then heating it to 880°C to 920°C and keeping it warm for 1.5h to 2.5h to obtain the first powder.

6. The method for preparing ordered porous carbon according to claim 1, characterized in that: The method for removing SiO2 in the first powder includes: placing the first powder in an alkaline solution, maintaining the solution at a second preset temperature for a fourth preset time and stirring the solution, thereby etching away SiO2 in the first powder to obtain a fifth solution.

7. The method for preparing ordered porous carbon according to claim 6, characterized in that: The method for obtaining the second powder includes: cooling the fifth solution to a fifth preset temperature, adjusting the pH value of the cooled fifth solution to neutral to obtain a sixth solution, and drying the sixth solution to obtain the second powder.

8. The method for preparing ordered porous carbon according to claim 1, characterized in that: The method for obtaining the fourth powder includes: activating the second powder with KOH to obtain a third powder, washing the third powder by suction filtration to obtain a neutral filtrate, and drying the neutral filtrate to obtain the fourth powder.

9. An ordered porous carbon, characterized in that: The porous carbon is obtained by the method according to any one of claims 1 to 8, and the general formula of the porous carbon is PFC-Si-XY, wherein X is the particle size of nano-SiO2, Y is the first preset value, and PFC is phenolic resin carbon.

10. The ordered porous carbon according to claim 9, characterized in that 15nm≤X≤25nm, 2wt%≤Y≤6wt%.